Arcade of focus - Lim, Su Hwee (2019)
Life unfolds every second, yet so often we let it slip away so easily. Living our lives worrying about the future or ruminate about the past. Also, we get distractible and interruptible at any moment by our smartphones that we had with us all day long. However, we seldom focus on what is happening at the moment, living through the actual moment. It is rare now for people to experience things without holding our mobile phones as we want to capture the “precious moment”.